Prevalence and Risk Factors of Substance Use Among Urban Adolescents: Questionnaire Study - Ljubotina, Damir (Array, 2004)
Aim. To examine the prevalence and possible interconnections between consuming various psychoactive substances. Also, to assess risk factors associated with the use of tobacco, alcohol, and marijuana among adolescents in Zagreb, Croatia. Method. We applied an anonymous, multi-dimensional, and self-reporting questionnaire to the representative sample of 2, 404 elementary and high-school students from Zagreb, Croatia. The questionnaire was designed to explore the extent to which examinees consume various psychoactive substances, as well as to assess their attitudes and knowledge about the substances. We collected data on socio-demographic characteristics of all examinees, their hierarchy of values, family relations, adjustment to school, relationships with peers, and high-risk and delinquent behavior. We analyzed the frequency and interconnections between consuming various psychoactive substances, as well as assessed the factors possibly predictive of consummation. Results. Almost 90% of all examinees claimed to have tried alcohol at least ones, 80% smoked tobacco, 39% experimented with marijuana, and 9% with Ecstasy. 36% consume alcohol, and 11% marijuana, several times a month ; 28% smoke tobacco daily. Although there is no significant difference in experimenting with psychoactive substances according to sex, day-to-day abuse is significantly more frequent among young men than women. About 43% believe smoking marijuana should become legally permitted, 37% are against this policy, and 21% are undecided on this issue. Our results show a high degree of interconnection between consummation of tobacco, alcohol, and marijuana. We also found that best predictive factors of consummation were a history of high-risk and delinquent behavior, troubled adjustment to school, domination of hedonistic values, and poor family relations. Regression analysis and pondering for ratios of particular predictors gave values for coefficients of multiple regression as follows: R=0.548 (R2=0.300 ; p<0.001) for tobacco, R=0.575 (R2=0.330 ; p<0.001) for alcohol, and R=0.608 (R2=0.370 ; p<0.001) for marijuana. Knowledge about consequences of consuming psychoactive substances positively correlated with the frequency of tobacco smoking (r=0.213, p<0.001), alcohol drinking (r=0.226, p<0.001), and consummation of marijuana (r=0.320, p<0.001). Conclusion. Most adolescents have had personal experiences with psychoactive substance abuse, but only a proportion became regular consumers. Most popular substances are alcohol, tobacco, and marijuana. We can even justifiably talk about a generalized tendency towards substance abuse among Zagreb adolescents. Assessed predictors account for 30-40% of variance in consummation of tobacco, alcohol, and marijuana. We propose our results are the empirical basis for re-evaluation of the current national program for preventing other forms of risk behaviour among children and adolescents.